Quantitative proteomic analysis of secretome of microbial consortium during saw dust utilization - Ravindran, Anita (2013)
Proteomics analysis of lignocellulolytic proteins by lignocellulosic biomass degrading microbes and compatible microbial consortium is a promising approach that offers a new means to enzyme discovery. The abundance of proteins in complex secretome by microbial communities would highlight key lignocellulolytic proteins for lignocellulosic biorefinery. In this study, lignocellulolytic enzymes of potent lignin degrading basidiomycota and effective cellulolytic ascomycota fungal strains, and their co-cultures were analyzed using high throughput isobaric tag for relative and absolute quantitation (iTRAQ) technique using liquid chromatography tandem mass spectrometry. Protein abundances in the iTRAQ-multiplexed samples were determined by integrating relative quantitation and exponentially modified protein abundance index (emPAI). The functional classification of the secretory proteins by individual culture and co-culture demonstrated 36.77% cellulolytic proteins, 13.06% hemicellulases, 14.09% ligninolytic proteins, 19.59% proteolytic enzymes. 7.22% hypothetical proteins and 6.87% cell morphogenesis proteins. The abundance of the proteins by individual cultures and co-cultured fungal consortium revealed that co-culturing of Phanerochaete chrysosporium with Trichoderma reesei QM6a and Trichoderma reesei Rut C30 induced the production of cellulolytic proteins and stimulated expression of hemicellulolytic enzymes. The hierarchical clustering of proteins in secretome of fungal strains and their co-cultures elucidated differential expressions of lignocellulolytic proteins by the microbial consortium.